Electron-microscopic study of a Mycoplasmatales virus, strain MV-Lg-pS2-L 172 - Liska, B; Tkadlecek, L (Folia microbiologica, 1975)
Morphology and adsorption of a globular virus, lysing Acholeplasma laidlawii were studied in ultrathin sections of plaques in a lawn of the host strain. The virus was globular, about 50 to 90 nm in diameter, with a clearly defined membrane, 6.5 to 8 nm thick. A protuberance about 25 to 35 nm long and 12 to 20 nm thick was observed on numerous virus particles. The evenly granulated, electron-optically dense content of the cells became clearer in cells affected by the viruses. Fibrillar structures of different thickness and small dense areas appeared in cells assumed to be in the preliminary stages of lysis. The interactions in the virus-host system and possible development stages of the virsu are discussed.
Keywords: Viral Plaque Assay; Microscopy, Electron; Viral Proteins; Adsorption; replikace viru; Bacteriophages; elektronová mikroskopie; bakteriolýza; lyzogenie; virové proteiny; plakové testy; Cytoplasm; Lysogeny; Virus Replication; Acholeplasma laidlawii; buněčná membrána; bakteriofágy; cytoplazma; Bacteriolysis; adsorpce; Cell Membrane